Determinants of Intention to Reuse Food Delivery Applications in Generation Z - Wenti Krisnawati; Mohammad Jufriyanto; Wasti Reviandani (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to answer the question of why someone uses FDA by using independent variables, namely special benefits, time saving, delivery experience, reviews and price value for reusing applications mediated by customer satisfaction. Total of 179 Generation Z respondents participated in this study. The design in this study uses quantitative and analytical techniques using PLS tools. Interesting findings in this study were successfully identified. This study found that time saving that is considered to be able to make people satisfied and return to reuse the FDA proved unacceptable, which means that in Generation Z there is perceived dissatisfaction with the time given by the FDA, and Generation Z does not need to save time in ordering food online, time saving is not a reason for them to reuse the FDA. In this case, online application food delivery service providers  must consider other causes that make them satisfied and willing to use the FDA application again, for example,  the special benefits offered, and the experience in ordering food, reviews and price values that are highly regarded by consumers, especially in generation Z which has an effect on customer satisfaction which in the end satisfaction affects the reuse of the application.